Perbandingan Pemahaman Mahasiswa dan Mahasiswi Kelas KPI A Semester 5 Dalam Menerima Pembelajaran Metode Penelitian Dakwah dan Komunikasi (Kuantitaif) - Rahman, Fitri Auliah; Nurfadillah; Nurul Khafifah; Iswan hidayat (Communication and Islamic Broadcasting Studies IAIN Parepare, 2024)
The ability to understand is needed by students in taking courses. This study aims to determine the comparison of students' and female students' understanding in receiving learning Da'wah and Communication Research Methods (quantitative), this research is a quantitative study. Data collected by questionnaire technique, respondents in this study were 30 respondents, 7 students and 23 female students of KPI A class semester 5 IAIN Parepare. Based on the results previously obtained, it was found that there was no difference in the understanding of KPI A class students and female students in semester 5 in receiving teaching research methods of da'wah and communication (quantitative).Keywords: understanding, learning, quantitative methods